Water Conservation and Sanitation HKBP Sidorame Private SMA - Vinolina, Noverita Sprinse; Rianna, Martha (Talenta Publisher, 2022)
This program is conducted to provide solutions to water conservation and sanitation problems that occur in HKBP Sidorame Private High School. The problem faced by the school is the slow absorption of water around the school yard so that floods often occur when it rains which causes disruption of the teaching and learning process. The service team conducted a site survey, provided socialization and motivation for students regarding the importance of a clean environment. The methods used are repairing damaged waterways and removing waste waste, making bioporous holes at a number of points in the school yard, dismantling and reassembling paving blocks where there were previously closed soil pores, planting plants to accelerate water absorption, renovation of water inlet routes. by increasing the height of the floor which is often the access for water to enter. The results obtained at this time, the school environment is free from puddles when it rains, the waste flow runs smoothly and the school environment is more beautiful. The actions that have been taken are very effective in overcoming the existing sanitation problems and motivate students to care about school hygiene and maintain it on an ongoing basis.